Effectiveness of educational materials on levels of knowledge of thyroid associated orbitopathy in an endocrinology clinic - Wajiha J. Kheir; Ali A. Khalil; Julien Torbey; Rachid Istambouli; Ramzi M. Alameddine (Elsevier, 2023)
Objective: We aim to assess and quantify basic knowledge about TAO in patients presenting to an endocrinology clinic and the effect of different educational materials on patients' knowledge. Methods: This study was conducted in a tertiary care center involving 255 patients presenting to an endocrinology clinic. The study was divided into three consecutive phases: 1. a control phase without any educational materials in the waiting room, 2. exposure to educational posters, and 3. exposure to educational pamphlets. Results: In the control population, only 16.5% of patients reported having knowledge of TAO, with a low average TAO-K score of 29.8 (out of 100). After the poster and pamphlet interventions, the percentage of patients having any knowledge of TAO increased across the control, poster and pamphlet phases: 16.5%, 25.9%, 63.5% respectively (p < 0.001). Similarly, the mean TAO-K score increased: 29.8, 45.8, 63.2 respectively (p < 0.001). Conclusion: This study confirms that patients with thyroid dysfunction have a low level of awareness and depth of knowledge of TAO. Innovation: We suggest the dissemination of educational material to increase the knowledge of TAO in thyroid patients. This will help with early symptom detection and ensure proper management of this interdisciplinary condition.